Direct Photodegradation of Androstenedione and Testosterone in Natural Sunlight: Inhibition by Dissolved Organic Matter and Reduction of Endocrine Disrupting Potential - Young, Robert B; Latch, Douglas E; Mawhinney, Douglas B; Nguyen, Thanh-Hoa; Davis, Jasmine C. C; Borch, Thomas (Environmental science & technology, 2013)
In surface waters, two of the most commonly observed androgenic steroid hormones are androstenedione (AD) and testosterone (T). This study compares the photodegradation of dilute (<10 μg L–1) aqueous solutions of AD and T in natural sunlight, and evaluates the endocrine-disrupting potential of the resulting solutions. This study also examines the effect of dissolved organic matter (DOM) on AD photodegradation. During spring and summer at Henderson, NV, USA (latitude 36.04°N), AD and T underwent direct photodegradation, with half-lives ranging from 3.7 to 10.8 h. In three model DOM solutions, AD’s half-life increased by 11% to 35%. Using screening factors to eliminate DOM’s inner filter effect, quantum yield calculations suggested that light screening was primarily responsible for AD’s increased half-life, and that physical quenching further inhibited AD’s photodegradation in two out of three DOM solutions. In vitro androgenic activity of the AD and T solutions decreased approximately as fast as AD and T were removed, suggesting that solar photodegradation reduces the risk of endocrine disruption in surface waters impacted by AD or T, subject to continuing inputs. Reduced in vitro androgenic activity appears to be related to steroid ring cleavage and the formation of highly oxidized photoproducts.